2009
DOI: 10.1007/s00109-009-0556-y
|View full text |Cite
|
Sign up to set email alerts
|

Fragment C of tetanus toxin, more than a carrier. Novel perspectives in non-viral ALS gene therapy

Abstract: The non-toxic carboxy-terminal fragment of tetanus toxin heavy chain (TTC) has been implicated in the activation of cascades responsible for trophic actions and neuroprotection by inhibition of apoptosis. Previous in vitro studies have described signalling pathways that underlie the administration of TTC to neurons. We investigated whether these properties were maintained in a mouse model of neurodegenerative disease. Naked DNA encoding for TTC was injected intramuscularly and neuromuscular function and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 33 publications
6
44
1
Order By: Relevance
“…For colocalizations, spinal MNs were labeled with Cy2-or Cy3-conjugated fluorotracer Nissl staining (1:200, Life Technologies, Grand Island, NY, USA). To quantify astroglial and microglial immunoreactivity, microphotographs of the grey matter of the ventral horn were taken at×400 and, after defining the threshold for background correction, the integrated density of glial fibrillary acidic protein (GFAP) or ionized calcium binding adaptor molecule 1 (Iba1) labeling was measured using ImageJ software (National Institutes of Health, Bethesda, MA, USA) [27,28]. The integrated density is the area above the threshold for the mean density minus the background.…”
Section: Treadmill Testmentioning
confidence: 99%
“…For colocalizations, spinal MNs were labeled with Cy2-or Cy3-conjugated fluorotracer Nissl staining (1:200, Life Technologies, Grand Island, NY, USA). To quantify astroglial and microglial immunoreactivity, microphotographs of the grey matter of the ventral horn were taken at×400 and, after defining the threshold for background correction, the integrated density of glial fibrillary acidic protein (GFAP) or ionized calcium binding adaptor molecule 1 (Iba1) labeling was measured using ImageJ software (National Institutes of Health, Bethesda, MA, USA) [27,28]. The integrated density is the area above the threshold for the mean density minus the background.…”
Section: Treadmill Testmentioning
confidence: 99%
“…Definitively, the neuroprotective role of fragment C has shed light on the understanding of the disease's neurodegeneration processes and the study of this promising property of TTC can be extended to other neurodegenerative diseases, such as Parkinson's disease, Alzheimer's disease and spinal muscular atrophy [75]. In summary, a successful neuroprotective treatment could transform neurodegenerative diseases from a relentless progressive and disabling disease to a problem that can be managed with only a modest effect on quality of life [76].…”
Section: More Update On Alsmentioning
confidence: 99%
“…More recently, the nature of TTC described by Longstreth and colleagues [62] and Larsen and colleagues [63], based on its stability to reach motor neurons specifically through the retrograde axonal transport system, has been reinforced as a potential neuroprotective agent in previous in vivo studies of gene and protein expression after injection of plasmid-DNA in transgenic SOD1 G93A mice, which carries the mutation G93A in human superoxide dismutase 1 (SOD1) [64]. These studies suggested that intramuscular naked-DNA TTC gene therapy administered into neurodegenerative mouse model delayed the onset of symptoms (by approximately 5 days), prolonged survival (by approximately 13 days) and improved the motor function activity in TTC-treated mice throughout disease progression, by increasing numbers of surviving motor neurons (Figure 2).…”
Section: Neuroprotective Nature Of Ttcmentioning
confidence: 99%
“…These studies suggested that intramuscular naked-DNA TTC gene therapy administered into neurodegenerative mouse model delayed the onset of symptoms (by approximately 5 days), prolonged survival (by approximately 13 days) and improved the motor function activity in TTC-treated mice throughout disease progression, by increasing numbers of surviving motor neurons (Figure 2). Apart from functional and survival results obtained in vivo in transgenic SOD1 G93A mice, the electrophysiological studies showed that, from three to four months of age, TTC treatment played a partial protective effect as demonstrated by the lower decline in amplitudes of the M waves, improvement in motor behavioral tests, and increased survival of motor neurons in the TTC-treated animals' lumbar spinal cord [64] (Figure 3). Interestingly, TTC administration can also affect antiapoptic pathways by means of calciumrelated mechanisms [64].…”
Section: Neuroprotective Nature Of Ttcmentioning
confidence: 99%
See 1 more Smart Citation